DINAMIKA PENYUSUNAN ANGGARAN DAERAH : KASUS PROSES PENETAPAN PROGRAM DAN ALOKASI ANGGARAN BELANJA DAERAH DI KABUPATEN SLEMAN - Hanida, Rozidateno Putri (Jurnal Penelitian Politik, 2016)
The article is a study of the dynamics of local budget arrangement especially in the process of program decision and local budget expenses allocation in Sleman region Other dynamics in this study is the establishment of egosectoral of division of planning namely SKPD in Sleman region In this regards planning proposal arranged by SKPD has not showed priority scale but rather compilation of proposal that are reserved from process of planning It can be said that the SKPD proposal is premature therefore SKPD attempts to reserve budget expenses without considering budget limitation and program continuation in other SKPD The dynamics in political process is legislative body in Sleman region that is oriented to constituent interests hence neglecting the benefit of a program and the value of trickle down effect of a program On both levels there have been dynamics that show interaction between actors by sharing and bargaining interests The implication of this dynamics is that budgeting policy cannot increase society welfare instantly and an effective and efficient budget is difficult to achieve